2002
DOI: 10.1038/sj.bjp.0704889
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of serum‐ and growth factor‐induced phenotypic changes in intact bovine tracheal smooth muscle

Abstract: 1 The present study aims to investigate whether phenotypic changes, reported to occur in cultured isolated airway smooth muscle (ASM) cells, are of relevance to intact ASM. Moreover, we aimed to gain insight into the signalling pathways involved. 2 Culturing of bovine tracheal smooth muscle (BTSM) strips for up to 8 days in the presence of 10% foetal bovine serum caused a time-dependent (t 1/2 =2.8 days) decrease in maximal contraction (E max ) to methacholine compared to serum-deprived controls (E max =74+4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
66
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 34 publications
(46 reference statements)
9
66
1
Order By: Relevance
“…Therefore, we assessed the expression of sm-myosin, calponin, and sm-␣-actin in homogenates prepared from BTSM strips treated with vehicle, collagen I, fibronectin, or laminin in the absence or presence of PDGF for 4 days. In accordance with our previous (8,9) and current observations that PDGF induces a shift towards a more proliferative (hypocontractile) phenotype, the growth factor reduced the expression of all contractile markers studied. Incubation with fibronectin or collagen I resulted in a reduction of contractile protein expression as well, which was both quantitatively and qualitatively similar to that induced by PDGF.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, we assessed the expression of sm-myosin, calponin, and sm-␣-actin in homogenates prepared from BTSM strips treated with vehicle, collagen I, fibronectin, or laminin in the absence or presence of PDGF for 4 days. In accordance with our previous (8,9) and current observations that PDGF induces a shift towards a more proliferative (hypocontractile) phenotype, the growth factor reduced the expression of all contractile markers studied. Incubation with fibronectin or collagen I resulted in a reduction of contractile protein expression as well, which was both quantitatively and qualitatively similar to that induced by PDGF.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found a strong correlation between the degree of change of E max , both with methacholine and KCl, induced by the applied ECM proteins in BTSM strips and the proliferative response by BTSM cells cultured on these proteins. Although determined using different experimental parameters measured in different (ASM tissue and cellular) conditions, this correlation was very striking and highly reminiscent of our previous findings (8). Together with the relationship between contractile protein expression and contractility found for the applied ECM proteins, these results indicate that ECM proteins are importantly involved in the regulation of ASM phenotype and function.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations